The answer would be one because .9998 would round the 9 to a 10 which would round the second 9 and then the third nine to make 1
Answer:
<h3>
![\boxed{ \bold{24}}](https://tex.z-dn.net/?f=%20%5Cboxed%7B%20%20%5Cbold%7B24%7D%7D)
</h3>
Step-by-step explanation:
![\mathsf{given}](https://tex.z-dn.net/?f=%20%5Cmathsf%7Bgiven%7D)
![\mathsf{hypotenuse(h) = 25}](https://tex.z-dn.net/?f=%20%5Cmathsf%7Bhypotenuse%28h%29%20%3D%2025%7D)
![\sf{perpendicular (p) = 7}](https://tex.z-dn.net/?f=%20%5Csf%7Bperpendicular%20%28p%29%20%3D%207%7D)
?
Now, Using Pythagoras theorem
![\sf{{h}^{2} = {p}^{2} + {b}^{2} }](https://tex.z-dn.net/?f=%20%5Csf%7B%7Bh%7D%5E%7B2%7D%20%20%3D%20%20%7Bp%7D%5E%7B2%7D%20%20%2B%20%20%7Bb%7D%5E%7B2%7D%20%7D)
plug the values
⇒![\sf{ {25}^{2} = {7}^{2} + {b}^{2} }](https://tex.z-dn.net/?f=%20%5Csf%7B%20%20%7B25%7D%5E%7B2%7D%20%20%3D%20%20%7B7%7D%5E%7B2%7D%20%20%2B%20%20%7Bb%7D%5E%7B2%7D%20%7D)
Evaluate the power
⇒![\sf{625 = 49 + {b}^{2} }](https://tex.z-dn.net/?f=%20%5Csf%7B625%20%3D%2049%20%2B%20%20%7Bb%7D%5E%7B2%7D%20%7D)
Swap the sides of the equation
⇒![\sf{49 + {b}^{2} = 625}](https://tex.z-dn.net/?f=%20%5Csf%7B49%20%2B%20%20%7Bb%7D%5E%7B2%7D%20%20%3D%20625%7D)
Move constant to right hand side and change it's sign
⇒![\sf{ {b}^{2} = 625 - 49}](https://tex.z-dn.net/?f=%20%5Csf%7B%20%7Bb%7D%5E%7B2%7D%20%20%3D%20625%20-%2049%7D)
Calculate the difference
⇒![\sf{ {b}^{2} = 576}](https://tex.z-dn.net/?f=%20%5Csf%7B%20%7Bb%7D%5E%7B2%7D%20%20%3D%20576%7D)
Squaring on both sides
⇒![\sf{b = 24}](https://tex.z-dn.net/?f=%20%5Csf%7Bb%20%3D%2024%7D)
Hope I helped!
Best regards!
36% = 36/100 divide both numerator and denominator by 4 gives you 9/25
It's important that you share the complete question. What is your goal here? Double check to ensure that you have copied the entire problem correctly.
The general equation of a circle is x^2 + y^2 = r^2. Here we know that the circle passes thru two points: (-3,2) and (1,5). Given that a third point on the circle is (-7, ? ), find the y-coordinate of this third point.
Subst. the known values (of the first point) into this equation: (-3)^2 + (2)^2 = r^2. Then 9 + 4 = 13 = r^2.
Let's check this. Assuming that the equation of this specific circle is
x^2 + y^2 = r^2 = 13, the point (1,5) must satisfy it.
(1)^2 + (5)^2 = 13 is not true, unfortunately.
(1)^2 + (5)^2 = 1 + 25 = 26 (very different from 13).
Check the original problem. If it's different from that which you have shared, share the correct version and come back here for further help.
Answer:
4+11=15
Step-by-step explanation:
c=4 11=b
4(c) + 11(d) = 15